2018
DOI: 10.1186/s12889-018-5565-8
|View full text |Cite
|
Sign up to set email alerts
|

Managing acute ischaemic stroke in a small island developing state: meeting the guidelines in Barbados

Abstract: BackgroundWe describe hospital-based management of acute ischaemic stroke patients in 2010–2013 in Barbados, by comparing documented treatment given in the single tertiary public hospital with international guideline recommendations.MethodsEvidence-based stroke management guidelines were identified through a systematic literature search. Comparisons were made between these guidelines and documented diagnostic practice (all strokes) and prescribed medication (ischaemic stroke only), using a combination of key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…Therefore, comparisons with other studies should be made with caution. In addition, results can differ from previous research because it is difficult to implement international guidelines in SIDS due to organizational differences [ 17 ].…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, comparisons with other studies should be made with caution. In addition, results can differ from previous research because it is difficult to implement international guidelines in SIDS due to organizational differences [ 17 ].…”
Section: Discussioncontrasting
confidence: 57%
“…All levels of stroke care facilities should have the capability of performing or access to either a cranial computed tomography (CT scan) or magnetic resonance imaging (MRI) scan within 30 min of the order being written with experienced physicians or a radiologist to interpret the imaging reports. Patients should also receive clinical diagnosis, CT brain scan, specialist evaluation by a multidisciplinary team and protocols should be made available for rt-PA use in acute stroke [45,46].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown an increase in the rehospitalization rate among IS patients caused by not adhering to the guideline recommendations for secondary stroke prevention. Studies have found a decline in the rehospitalization rate of stroke patients as they followed the guideline recommendations [6][7][8][9][10]. According to a retrospective cohort study, patients who were discharged after IS with secondary stroke prevention therapies in the short and long term will help reduce the risk of recurrent stroke [10].…”
Section: Introductionmentioning
confidence: 99%